ANALISIS PENERAPAN PERMENDAGRI NOMOR 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA: ANALISIS PENERAPAN PERMENDAGRI NOMOR 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA - Zulkarnain Zulkarnain; Widi Nurdiati (Jurnal Akuntansi Bisnis dan Ekonomi, 2020)
This study aims to determine the application of Permendagri No. 113/2014 concerning Village Financial Management in Bojongasih Village, Parakansalak District, Sukabumi Regency which includes planning, administration, implementation, reporting, accountability, and guidance and supervision of village financial management. The qualitative-descriptive method is used to describe and interpret data regarding village financial management found in the field and then draw a conclusion. Data collection was carried out by documentation study and interviews. Then the data analysis technique is how to reduce, present and verify the data. The results of this study are that in general the financial management of Bojongasih Village, Parakansalak District, Sukabumi Regency is not fully in accordance with Permendagri No. 113/2014. Some of the obstacles faced include in the Village planning that it is not timely to submit the Raperdes regarding the APBDesa. In the implementation of financial management it is against the Permendagri and not in accordance with the Permendagri. Then, the monthly reports are not submitted to the Village Head. As well as less than optimal guidance and supervision from local governments.